Implementation of Environmental Management System: A Case Study for Construction Companies in the Philippines - Marlon C. Leyesa (Engineering Proceedings, 2024)
This study aims to design an environmental management information system (EMIS) by integrating all necessary environmental documents for project implementation based on ISO 14001:2015 and using an exploratory sequential mixed method of research. The agile project management methodology was also used to speculate how a project must be managed using environmental information. The problems with the current operation in compliance with ISO 14001:2015 were addressed using EMIS with the participation of IT professionals. The end-users assessed the functionality, efficiency, compatibility, usability, reliability, security, maintainability, and portability of EMIS. A computer system is required for EMIS for accurate and effective document storage and updates. EMIS can be developed based on coding and simulation to make it simpler to save, retrieve, and update documents. EMIS needs to have functionality, efficiency, compatibility, usability, reliability, security, maintainability, and portability.